The Effect of Social Media Addiction, Nomophobia, and Netlessphobia on Students' Online Shopping Addictions During the Covid-19 Pandemic - Dilşad Güzel; Muhammet Mutlu (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
The excessive use of internet-based technologies and social media platforms during the COVID-19 pandemic has caused problems such as social media addiction, nomophobia, netlesphobia, and online shopping addiction in individuals. This research aims to examine whether social media addiction, nomophobia, and netlessphobia affect students' online shopping addiction. An online survey was conducted on 439 students to test the research model and hypotheses. SPSS 25.0 packet program was used, and reliability, exploratory factor analysis, descriptive analyses, correlation and multiple regression analysis were applied to the data. Multiple regression analysis results revealed that social media addiction, nomophobia, and netless phobia influence students' online shopping addiction.